Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Effects of Five Serial Apnoeas Prior to a Running Time Trial in Competitive Athletes - Matthew John Barlow; Catherine Ross; Remmie Cockrell; Morgan Rubie; Harry Cahill; Craig Robertson; Jamie French; Antonis Elia (Journal of Science in Sport and Exercise, 2025)
Purpose This study aimed to determine whether a series of repeated maximal voluntary apnoeas is effective in improving subsequent time trial performance in competitive level track and field athletes. Methods Seventeen competitive runners volunteered for this study and based on their preferred competitive distance they were placed either in the 200 m (5 male, 4 female) or 1000 m group (3 male, 5 female). On two separate occasions (≤ 7 days apart), the participants performed a running time-trial that was preceded either by: (i) a standardised warm up (WO) or (ii) a standardised warm up succeeded by five repeated maximal dry static apnoeas (WA). Splenic volume, haematology and cardiovascular parameters were monitor at rest, before and after each time-trial. Results WA resulted in a significantly faster performance (27.51 ± 3.49 s; P = 0.009) compared with WO (27.96 ± 3.34 s) in the 200 m group, whereas no differences were observed in the 1000 m group (WA, 211.10 ± 26.18 s; WO, 215.82 ± 25.13 s, P = 0.120). No differences were noted in splenic volume between WO and WA in either group ( P ≥ 0.081). Haemoglobin was significantly elevated after breath-holding in the 200 m (+ 7 g/dL, P = 0.041) but not 1000 m group. Conclusion This study demonstrates that five repeated maximal apnoeas are capable of significantly improving a 200 m but not a 1000 m time-trial performance in competitive track and field athletes.

The effect of pregnancy, heat stress and altrenogest supplementation on the porcine mid-luteal phase corpus luteum proteome - R. Blythe Schultz; Malavika K. Adur; Zoë E. Kiefer; Jamie M. Studer; Katie L. Bidne; Matthew R. Romoser; Lance H. Baumgard; Aileen F. Keating; Jason W. Ross (Theriogenology, 2025)

Grazing management and edapho-climatic factors: drivers of soil carbon and vegetation dynamics in South African rangelands - Elmarie Kotzé; Jamie Paulse-Ross; Paul J Malan; Angelinus C Franke (Plant and Soil, 2025)
Aims Rangelands serve as key reservoirs of soil organic carbon (C) and play a crucial role in global C cycling. High-density grazing (HG) systems gained popularity in South Africa, promoting sustainable grazing and higher animal productivity per unit area. HG systems typically implement intense grazing pressure followed by extended resting periods for vegetation recovery, in contrast to conventional rotational grazing systems (CG) applying lower grazing pressure over a longer period. This study quantified soil and vegetation differences between HG and CG systems and aimed to gain insights into underlying mechanisms. Methods A fence-line comparison was performed on 11 sites in four semi-arid, summer rainfall regions: North West, Eastern Cape, eastern Free State, and central Free State. Each site represented two neighbouring commercial rangeland farms (HG vs CG). Soil samples were collected along fence-lines between the two farms and analysed for bulk density, aggregate stability, total C and nitrogen, organic material, active C, soil microbial biomass. Vegetation indicators, including root biomass, veld condition, and Normalized Difference Vegetation Index (NDVI) were also assessed. Results HG had positive effects on soil and vegetation, especially in fine-textured soils and wetter climates. Exudates from improved grass roots under HG systems enhanced soil microbial activity and C sequestration. However, a significantly negative impact of increased stocking rates on bulk density, particularly in deeper soil layers, was found across regions. Conclusions This study highlights the effects of grazing systems on soil and vegetation dynamics, emphasizing the importance of site-specific conditions in shaping these effects.

Inshore and offshore marine migration pathways of Atlantic salmon post‐smolts from multiple rivers in Scotland, England, Northern Ireland, and Ireland - Jessica R. Rodger; Jessie Lilly; Hannele M. Honkanen; Diego del Villar; Richard Kennedy; Niall Ó. Maoiléidigh; Patrick Boylan; Robert Rosell; David J. Morris; Ross O'Neill; Catherine Waters; Deirdre Cotter; et al. (Journal of Fish Biology, 2025)
The migratory behavior of Atlantic salmon ( Salmo salar ) post‐smolts in coastal waters is poorly understood. In this collaborative study, 1914 smolts, from 25 rivers, in four countries were tagged with acoustic transmitters during a single seasonal migration. In total, 1105 post‐smolts entered the marine study areas and 438 (39.6%) were detected on a network of 414 marine acoustic receivers and an autonomous underwater vehicle. Migration pathways (defined as the shortest distance between two detections) of up to 575 km and over 100 days at sea were described for all 25 populations. Post‐smolts from different rivers, as well as individuals from the same river, used different pathways in coastal waters. Although difficult to generalize to all rivers, at least during the year of this study, no tagged post‐smolts from rivers draining into the Irish Sea were detected entering the areas of sea between the Hebrides and mainland Scotland, which is associated with a high density of finfish aquaculture. An important outcome of this study is that a high proportion of post‐smolts crossed through multiple legislative jurisdictions and boundaries during their migration. This study provides the basis for spatially explicit assessment of the impact risk of coastal pressures on salmon during their first migration to sea.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Identification of Albopleistophora grylli n. gen. n. sp. (Microsporidia) and its impact on crickets (Gryllus spp.) in food-and-feed culture systems - Edouard Bessette; Jamie Bojko; Kelly S. Bateman; Stuart Ross; Nicolai V. Meyling; Bryony A.P. Williams (Journal of Invertebrate Pathology, 2025)

Autumn outmigrants in brown trout ( Salmo trutta ) are not a demographic dead‐end - Robert Wynne; Joshka Kaufmann; Jamie Coughlan; Karl. P. Phillips; Catherine Waters; Ross W. Finlay; Ger Rogan; Russell Poole; Philip McGinnity; Thomas E. Reed (Journal of Fish Biology, 2023)
Genetic identity analysis and PIT (passive integrated transponder) tagging were used to examine the freshwater return rates and phenotypic characteristics of n = 1791 downstream migrating juvenile Salmo trutta in the Burrishoole catchment (northwest Ireland) across the period September 2017 to December 2020. In this system, juveniles out‐migrate (move from freshwater into brackish or marine habitats) in every month of the year, with distinct seasonal peaks in spring (March through June; mostly silvered smolts) and autumn (September through December; mostly younger, unsilvered fry or parr). Both types exhibited a sex‐bias towards females, which was stronger in spring (78% females) than in autumn outmigrants (67%). Sixty‐nine returning fish were matched back to previous juvenile outmigrants, and similar return rates were found for spring outmigrants (5.0%), autumn outmigrants (3.3%) and fish that out‐migrated outside of spring or autumn (2.8%). Spring and autumn outmigrants returned at similar dates (typically mid to late July), but autumn fish were away for longer periods (median = 612 days; spring outmigrants = 104 days). Autumn outmigrants were 25% smaller than spring outmigrants at outmigration and 6% smaller on their return, and within both groups smaller/younger outmigrants spent longer away than larger/older outmigrants. Autumn outmigrants were more likely to return unsilvered as “slob” trout (84%) than spring outmigrants (31%), suggesting they make greater use of brackish habitats that might be safer, but less productive, than fully marine habitats. Nonetheless, both types also produced silvered “sea trout” (≥1+ sea‐age), implying neither is locked into a single life‐history strategy. The findings emphasise that autumn outmigrants and the transitional habitats that support their persistence should not be overlooked in salmonid management and conservation.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

The Supportive Care Needs of Cancer Patients: a Systematic Review - Madeleine Evans Webb; Elizabeth Murray; Zane William Younger; Henry Goodfellow; Jamie Ross (Journal of Cancer Education, 2021)
Cancer, and the complex nature of treatment, has a profound impact on lives of patients and their families. Subsequently, cancer patients have a wide range of needs. This study aims to identify and synthesise cancer patients’ views about areas where they need support throughout their care. A systematic search of the literature from PsycInfo, Embase and Medline databases was conducted, and a narrative. Synthesis of results was carried out using the Corbin & Strauss “3 lines of work” framework. For each line of work, a group of key common needs were identified. For illness-work, the key needs idenitified were; understanding their illness and treatment options, knowing what to expect, communication with healthcare professionals, and staying well. In regards to everyday work, patients wanted to maintain a sense of normalcy and look after their loved ones. For biographical work, patients commonly struggled with the emotion impact of illness and a lack of control over their lives. Spiritual, sexual and financial problems were less universal. For some types of support, demographic factors influenced the level of need reported. While all patients are unique, there are a clear set of issues that are common to a majority of cancer journeys. To improve care, these needs should be prioritised by healthcare practitioners.

Predicting biodiversity richness in rapidly changing landscapes: climate, low human pressure or protection as salvation? - David W. Macdonald; Luca Chiaverini; Helen M. Bothwell; Żaneta Kaszta; Eric Ash; Gilmoore Bolongon; Özgün Emre Can; Ahimsa Campos-Arceiz; Phan Channa; Gopalasamy Reuben Clements; Andrew J. Hearn; Laurie Hedges; et al. (Biodiversity and Conservation, 2020)
Rates of biodiversity loss in Southeast Asia are among the highest in the world, and the Indo-Burma and South-Central China Biodiversity Hotspots rank among the world’s most threatened. Developing robust multi-species conservation models is critical for stemming biodiversity loss both here and globally. We used a large and geographically extensive remote-camera survey and multi-scale, multivariate optimization species distribution modelling to investigate the factors driving biodiversity across these two adjoining biodiversity hotspots. Four major findings emerged from the work. (i) We identified clear spatial patterns of species richness, with two main biodiverse centres in the Thai-Malay Peninsula and in the mountainous region of Southwest China. (ii) Carnivores in particular, and large ungulates to a lesser degree, were the strongest indicators of species richness. (iii) Climate had the largest effect on biodiversity, followed by protected status and human footprint. (iv) Gap analysis between the biodiversity model and the current system of protected areas revealed that the majority of areas supporting the highest predicted biodiversity are not protected. Our results highlighted several key locations that should be prioritized for expanding the protected area network to maximize conservation effectiveness. We demonstrated the importance of switching from single-species to multi-species approaches to highlight areas of high priority for biodiversity conservation. In addition, since these areas mostly occur over multiple countries, we also advocate for a paradigmatic focus on transboundary conservation planning.

Assessing risks and mitigating impacts of harmful algal blooms on mariculture and marine fisheries - Andrew Ross Brown; Martin Lilley; Jamie Shutler; Chris Lowe; Yuri Artioli; Ricardo Torres; Elisa Berdalet; Charles R. Tyler (Reviews in Aquaculture, 2020)
Aquaculture is the fastest growing food sector globally and protein provisioning from aquaculture now exceeds that from wild capture fisheries. There is clear potential for the further expansion of marine aquaculture (mariculture), but there are associated risks. Some naturally occurring algae can proliferate under certain environmental conditions, causing deoxygenation of seawater, or releasing toxic compounds (phycotoxins), which can harm wild and cultured finfish and shellfish, and also human consumers. The impacts of these so‐called harmful algal blooms ( HAB s) amount to approximately 8 $billion/yr globally, due to mass mortalities in finfish, harvesting bans preventing the sale of shellfish that have accumulated unsafe levels of HAB phycotoxins and unavoided human health costs. Here, we provide a critical review and analysis of HAB impacts on mariculture (and wild capture fisheries) and recommend research to identify ways to minimise their impacts to the industry. We examine causal factors for HAB development in inshore versus offshore locations and consider how mariculture itself, in its various forms, may exacerbate or mitigate HAB risk. From a management perspective, there is considerable scope for strategic siting of offshore mariculture and holistic Environmental Approaches for Aquaculture, such as offsetting nutrient outputs from finfish farming, via the co‐location of extractive shellfish and macroalgae. Such pre‐emptive, ecosystem‐based approaches are preferable to reactive physical, chemical or microbiological control measures aiming to remove or neutralise HAB s and their phycotxins. To facilitate mariculture expansion and long‐term sustainability, it is also essential to evaluate HAB risk in conjunction with climate change.

Sampling, extraction and incidence of redberry mites (Acalitus essigi) on blackberries in Australia - Hui Meng Law; Geoff R. Allen; Jamie T. Davies; Ross Corkrey; Michele Buntain; Stephen R. Quarrell (Experimental and Applied Acarology, 2020)

Gap junctions modulate seizures in a mean-field model of general anesthesia for the cortex - Moira L. Steyn-Ross; D. Alistair Steyn-Ross; Jamie W. Sleigh (Cognitive Neurodynamics, 2012)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

The Effect of Bleaching on the Terpene Chemistry of Plexaurella fusifera: Evidence that Zooxanthellae Are Not Responsible for Sesquiterpene Production - Jamie L. Frenz-Ross; Julie J. Enticknap; Russell G. Kerr (Marine Biotechnology, 2008)

A transgene for high methionine protein is posttranscriptionally regulated by methionine - Suman Bagga; Carol Potenza; Jamie Ross; Melinda N. Martin; Thomas Leustek; Champa Sengupta-Gopalan (In Vitro Cellular & Developmental Biology - Plant, 2005)